DESAIN TATA KELOLA REKAM MEDIS ELEKTRONIK KUNJUNGAN PASIEN UNIT GAWAT DARURAT GUNA MENUNJANG PELAPORAN KUNJUNGAN PASIEN DENGAN V-MODEL - Dwi Anjeli, Rieke; Syahidin, Yuda; Yunengsih, Yuyun (Jurnal Infokes, 2023)
This research aimed to determine of patients’ visit information system in emergency unit using V-Model. In this research method used is qualitative method with descriptive approach. Data collection techniques used is by observations, interviews, and literature studies which had relation to the subject. Software methods used is V-Model. From the research and observations made there were problems in the reporting section of the visit, namely the processing of patient visits an emergency unit is still done by looking at the data from the registry books patient emergency unit and data to be processed using Microsoft Excel so it took a long time. Suggestions given were by: 1) providing a computer unit at the emergency unit in particular for reporting of patient visits did not to be done manually, and 2) designing information system which help job quickly and accurately. Keywords: Designing, Information System, Patients Visits, Emergency Unit, V-Model.